On the Safety of Human Body Communication - Maity, Shovan; Nath, Mayukh; Bhattacharya, Gargi; Chatterjee, Baibhab; Sen, Shreyas (IEEE transactions on biomedical engineering, 2020)
Human Body Communication (HBC) utilizes the electrical conductivity properties of the human body to communicate between devices in and around the body. The increased energy-efficiency and security provided by HBC compared to traditional radio wave based communication makes it a promising alternative to communicate between energy constrained wearable and implantable devices around the body.However, HBC requires electrical signals to be transmitted through the body, which makes it essential to have a thorough analysis of the safety aspects of such transmission. This paper looks into the compliance of the current density and electric/magnetic fields generated in different modalities of HBC with the established safety standards. Circuit and Finite Element Method (FEM) based simulations are carried out to quantitatively find the compliance of current density and fields with the established safety limits. The results show the currents and fields in capacitive HBC are orders of magnitude smaller than the specified limits. However, certain excitation modalties in galvanic HBC can result in current densities and fields exceeding the safety limits around the excitation point on the body near the electrode. A study with 7 human subjects (4 male, 3 female) is carried out over a month, using capacitive HBC.The study monitors the change in 5 vital parameters (Heart Rate, Mean Arterial Pressure, Respiration Rate, Peripheral Capillary Oxygen Saturation, Temperature), while wearing a HBC enabled device. Analysis of the acquired data statistically shows no significant change in any of the vital parameters of the subjects, confirming the results of the simulation study.